Architecture for multi-party synchronization of data sets in a distributed environment - Marczewski, Marcin (Trinity College Dublin. Department of Computer Science, 2005)
In the world of common mobility, where more and more people and organizations use various mobile equipment such as phones, personal data assistants and other devices the consistency of stored and exchanged data is a very important thing. Today the flow of information, especially in business processes, can be very high and valuable, and deformation of this data is unacceptable because it can lead to numerous misunderstandings. The use of mobile devices and networked computers makes people want to have the same data on all these devices. In case where a large number of devices stores huge data sets which can be modified by hundreds of people, simple data copying is highly unprofitable and time-consuming. Nowadays, we can find a lot of various algorithms for set reconciliation designed for various environments, devices. These algorithms have a variety of advantages, but they also have a number of disadvantages which can limit their usefulness. In this work, a few existing data synchronization algorithms are investigated and compared. Their usefulness for various scenarios is described and analyzed. What is more, this dissertation project also presents various gossip protocols which can be used to disseminate messages in a network environment. Finally, an architecture for multi-party synchronization of data sets in a network environment is designed, implemented and examined by number of experiments with various settings.
Keywords: Computer Science